(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
The research deals with Paul Ricoeur’s hermeneutic philosophy of the concept of narration and its connection to life, time and self-identity, in that self engaged in practice and action, whose personal and even collective life can only be accessed in the narrative anecodotal plot of an entire life of a speaker and active self and what it narrates ultimately constitutes her narrative identity presented by Paul Ricoeur as a solution to a fixed ’sameness’ identity that doesn’t accept change and a ’self’ identity that changes and remains self-preserving.